Natural Balance of Power, The Balance of Power Between Countries that Promote Economic - Hutasoit, SE., MSi., MSE, Posma Sariguna Johnson Kennedy (Universitas Kristen Indonesia, 2016)
Traditionally, external threat comes from the asymmetrical military power among countries, where the concept has now evolved into a natural balance of power. In this paper, the analysis of natural balance of power will be done through a literature review. Today, modern threats are always connected to the military force that is proportional to economy of a country. The level of militarization, which is too high and out of proportion with the ability of economies, perceived as a threat to countries in the vicinity. Instead strength in the economy with healthy competition is expected as a national power. Who owns the defense along with the strong economy was the one who could control the international relations in the strategic environment.Keywords : economic of defence, natural balance of power, strategic environment